The complete mitogenome of Metopograpsus quadridentatus and phylogenetic analysis. Issue 2 (3rd July 2018) - Wang, Zhengfei; Ji, Chenyao; Wang, Ziqian; Tang, Dan; Wu, Qiong; Guo, Huayun; Tao, Yitao
Abstract: The complete mitochondrial genome of Metopograpsus quadridentatus was determined to be 15, 520 bp in length. It consists of 13 protein-coding genes, 22 transfer RNAs, 2 ribosomal RNAs and a control region. There are 13 overlapping regions in the genome with 1 to 25 bp length. The largest overlapping region is located between nad1 and trnL1 . The AT-skew and GC-skew for the whole mitogenome are both negative, indicating a higher occurrence of Ts than As and Cs than Gs. The molecular data here we presented could play a useful role to study the evolutionary relationships and population genetics of Grapsidae crabs.